Pengaruh Pembiasaan Shalat Dhuha Berjamaah Dalam Pembentukkan Kedisiplinan Siswa di MTs Insan Sejati Bogor - Sulis Setiawati; Salati Asmahasanah; Dewi Anggrayni (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
This study aims to determine the implementation of dhuha prayer activities at MTs Insan Sejati, and the discipline within the school. In addition, this study aims to determine the extent of the role of dhuha prayer activities in shaping student discipline at MTs Insan Sejati. So that it can be obtained the percentage of the extent to which this dhuha prayer activity affects student discipline in everyday life. In this study, the method used is the correlation method, so that it will be obtained whether there is a relationship between the independent variable (Dhuha Prayer) and the dependent variable (Student Discipline), the subjects in this study were all 70 students of MTs Insan Sejati. The results of the calculation of the correlation coefficient between the dhuha prayer activity variable (X) and the student discipline variable (Y) obtained an rcount of 0.850. Thus, when compared to the value of rcount with rtable, by taking a significance level of 5% and degrees of freedom N – 2 = 70 – 2 = 68. Based on the results of rxy and rtable values ​​at a significance level of 5%, the results obtained are rcount of 0.850 and rtable of 0.250. Thus, the value of rcount > rtable = 0.850 > 0.250. This shows that Ha is accepted and Ho is rejected, meaning that there is a significant influence between the congregational dhuha prayer (X) on student discipline (Y). Keywords: Dhuha Prayer, Student Discipline